Errors Analysis of Directive Speech Act and Politeness Strategy in Kaiwa Chukyu Learning - Diner, Lispridona (Bina Nusantara University, 2020)
The research aimed to explain types of directive speech act encompassed meirei (order), irai (plea), kinshi (prohibition), kyoka (permit), and teian (suggestion) in the Japanese language. Directive speech acts were common for students in the kaiwa chukyu zenhan level (basic intermediate speaking lesson). The present research employed a listening method with the basic technique, i.e., tapping method. Further, involved and uninvolved conversation observation techniques, note-taking, and recording were applied to collect the data. The data object was the documentation of student conversations in class. The data, consisting of the directive speech act of the politeness principles in the conversation during the Japanese course kaiwa chukyu zenhan, were analyzed using an identity method. In conclusion, the research identifies several directive speech acts that are used during the class. Those are zenhan (order, three data), requesting (two data), suggesting (one data), prohibiting (one data), and permitting (one data). Moreover, the honorifics used include the teineigo and kenjogo. Among the nine data, directive speech acts are identified in the class, and only one data indicates the indirect speech act.